Documenting its applications in quantity surveying research: a review - Bandi, Shamsul Hadi; Abdullah, Fadhlin (Faculti Alam Bina, UTM, Malaysia, 2016)
Literature review is an indispensable segment in scholarly undertaking. Although important, it appears that little has been documented about its process especially from the perspective of research in quantity surveying. This despite such effort could possibly benefit novices attempting to explore the vast territory of quantity surveying intellectual domain. Hence, drawing from the author’s recent research in identifying the issues that have impeded the use of the bills of quantities (BQ), this paper aims to document the steps involved in the process of reviewing literatures concerning the research. Accordingly, a nuts-and-bolts approach to literature review has been put forward in the background and it strives to describe the steps following the review processes carried out in the research underpinning this paper. This paper reflects that the process for reviewing the literature could be viewed as iterative-cyclical. In this regard, searching; mapping; analysing and synthesising have been recognised as the important steps in the process. The paper also demonstrates that the use of NVivo assisted greatly in the process and adds significant value through its pragmatic features and useful displays. The paper discussed these processes in relation to research in quantity surveying which is significant to the domain or a part thereof.